2020
DOI: 10.3390/jpm10040160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chromosome Microarray Analysis in a Large Cohort of Females with Autism Spectrum Disorders: A Single Center Italian Study

Abstract: Autism spectrum disorders (ASD) encompass a heterogeneous group of neurodevelopmental disorders resulting from the complex interaction between genetic and environmental factors. Thanks to the chromosome microarray analysis (CMA) in clinical practice, the accurate identification and characterization of submicroscopic deletions/duplications (copy number variants, CNVs) associated with ASD was made possible. However, the widely acknowledged excess of males on the autism spectrum reflects on a paucity of CMA studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…6 The relationship between duplication of the 22q11 region and psychosis or dementia is relatively ambiguous. Duplications are detected in 1 in 700 individuals with developmental disorders, often inherited in an autosomal dominant manner (OMIM:608363), with concomitant intellectual disability, facial dysmorphism, stunted growth, Attention deficit hyperactivity disorder, autism, 7,8 and severe psychoses. 9 There is no history of any developmental deficits or intellectual disability in this patient, and the physical examination had not revealed any dysmorphic features.…”
Section: Discussionmentioning
confidence: 99%
“…6 The relationship between duplication of the 22q11 region and psychosis or dementia is relatively ambiguous. Duplications are detected in 1 in 700 individuals with developmental disorders, often inherited in an autosomal dominant manner (OMIM:608363), with concomitant intellectual disability, facial dysmorphism, stunted growth, Attention deficit hyperactivity disorder, autism, 7,8 and severe psychoses. 9 There is no history of any developmental deficits or intellectual disability in this patient, and the physical examination had not revealed any dysmorphic features.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, researchers have postulated personalized medicine approaches for individuals with ASD owing to their specific and unique characteristics. Regardless of the various approaches utilized by different researchers, the majority of these studies have concluded that patients with ASD are unique in many ways, and hence, require a personalized approach for the amelioration of ASD symptoms [ 189 ]. In this section, we have attempted to describe the unique mitochondrial dysfunctions in ASD patients and hence their potential targeting using precision personalized mitochondrial medicine.…”
Section: Mitochondria Drug Targeting Rationale For Autism Spectrum Di...mentioning
confidence: 99%
“…Previous studies on abnormal copy number variation (CNV) in patients with mental retardation and multiple malformations have shown that the symptoms of some patients may be related to 16p13.11 microdeletion/microduplication [6][7][8]. It was reported that in addition to microcephaly, developmental delay and a series of mental disorders, patients with 16p13.11 microdeletion also reported a series of epilepsy, while those with 16p13.11 microduplication showed mental retardation, autism, epilepsy and deformative features [9,10].…”
Section: Introductionmentioning
confidence: 99%